2010
DOI: 10.1097/cji.0b013e3181fad2b0
|View full text |Cite
|
Sign up to set email alerts
|

Selection of CD8+PD-1+ Lymphocytes in Fresh Human Melanomas Enriches for Tumor-reactive T Cells

Abstract: CD8 + Tumor infiltrating lymphocyte (TIL) in human melanomas express high levels of PD-1 and are functionally impaired. However, adoptive cell therapy using in vitro-expanded TIL can be a highly effective therapy for patients with advanced melanoma. This discrepancy led us to further analyze the CD8 + PD-1 + TILs. We found that the percentage of PD-1 expressing CD8 + T-cells was higher in the tumor digests that generate tumor-reactive TILs after in vitro culture in IL-2 (P=0.0007). Also sorted and expanded CD8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
146
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 189 publications
(162 citation statements)
references
References 24 publications
15
146
1
Order By: Relevance
“…A similar scenario has recently been described in melanoma, where PD-1 was shown to specifically demarcate tumor-reactive CD8 T cells (51). Importantly, in this study, PD-1 expression on melanoma-derived TIL was shown to be rapidly downregulated after in vitro expansion, and these "reinvigorated" TIL mediated profound clinical effects after reinfusion into melanoma patients (52). If this latter finding is also applicable to ovarian cancer, then it bodes well for the possibility of using in vitro expanded PD-1 þ CD103 þ TIL for the treatment of this lethal disease.…”
Section: Discussionsupporting
confidence: 48%
“…A similar scenario has recently been described in melanoma, where PD-1 was shown to specifically demarcate tumor-reactive CD8 T cells (51). Importantly, in this study, PD-1 expression on melanoma-derived TIL was shown to be rapidly downregulated after in vitro expansion, and these "reinvigorated" TIL mediated profound clinical effects after reinfusion into melanoma patients (52). If this latter finding is also applicable to ovarian cancer, then it bodes well for the possibility of using in vitro expanded PD-1 þ CD103 þ TIL for the treatment of this lethal disease.…”
Section: Discussionsupporting
confidence: 48%
“…Functional experiments conducted ex vivo revealed that CD160 [38][39][40] we suggest that treatments involving disruption of PD-1/PD-L1 interaction by means of blocking antibodies might impact positively on the clinical outcome of ACT using geneengineered T cells. Moreover, it has been reported that PD-L1 is induced by IFNg in antigen-presenting cells 41 and melanoma cells, 42 and that PD-L1 expression in melanoma cells is higher in areas of the tumor presenting a higher T-cell infiltration, 43 suggesting that PD-L1 expression in the tumor microenvironment might be increased after ACT.…”
Section: Discussionmentioning
confidence: 99%
“…The notion that PD-1 expression on Tfh cells elicits context-dependent responses in protected lymphoid structures is supported by a recent murine study showing that PD-1 + Tfh cells survive and function in gut-associated lymphoid follicles after anti-Thy-1 antibody treatment (54). PD-1 expression is often considered a sign of T cell exhaustion; however, our expanding knowledge indicates that it can also act as a signal for other functions, highlighted by the demonstration that CD8 + PD-1 + TIL produce higher levels of IFN-γ than PD-1 -cells (55). Overall, current data suggests that, in contrast to effector T cell TIL, PD-1 + Tfh cells located in BC-associated TLS likely do not contact PD-L1 + tumor cells and are not directly affected by PD-1-mediated tumor suppression but are instead regulated by PD-1 to elicit other functions.…”
Section: Discussionmentioning
confidence: 99%